The Effect the Training Program on Dementia Has on the Knowledge and Attitude of Nursing College Students towards Dementia and Attitude towards the Caring of the Elderly (Medico Legal Update, 2019)
Background/Objectives: This study aims to investigate the effects of dementia education program on the knowledge and attitude to the dementia, and caring attitude to the elderly people in the nursing university students.Method/Statistical Analysis: 122 nursing students in Seniors of Nursing University located in M City were selected as the subjects and 12-hours dementia education program for 5 times were performed in the education group. They were analyzed by frequency, percentage, and T-test for independent sample using SPSS/WIN 22.0 program.Findings: Upon the results, the education group showed higher knowledge on dementia with 13.25 points, but not statistically significant (p=.621). With respect to the attitude to dementia, mean score in the education group was 4.01 points which was more positive attitude to the dementia to the elderly with statistically significant difference (p=.027). Regarding caring attitude to the elderly, the education group showed 3.78 points as a mean score to be more positive with statistical significance (p=.003).Improvements/Applications: From these results, dementia education program demonstrated the effects to change the attitude to dementia and caring the elderly positively. Therefore, it is required to seek the improvement plans of nursing quality by enhancing the knowledge and understanding on dementia in the nursing students upon development of dementia education program together with theory and practices.